Top-Ten Tips for Imaging the ACL - Griffith, James F.; Ng, Alex W.H. (Seminars in Musculoskeletal Radiology, 2019)
Tears of the anterior cruciate ligament (ACL) are common and represent a serious injury. Although diagnosis on magnetic resonance imaging (MRI) is usually straightforward, diagnostic difficulty can occasionally arise. This review provides tips for imaging the ACL in those scenarios where a confident diagnosis is not possible on standard MRI of the knee. Potential pitfalls while imaging the ACL are also discussed.
Keywords: anterior cruciate ligament; ligament; magnetic resonance imaging; tear; anatomy